Pengaruh Senam Lansia terhadap Kebugaran Jasmani Lansia di Desa Tanjung Kecamatan Hamparan Rawang Kota Sungai Penuh - Edo Yuliandra Pratama; Muhammad Hidayat Z; Winda Lestari (Departement of Mathematics Education, 2023)
Physical fitness which is said to be the ability to be able to carry out activities without experiencing significant fatigue. One of the most frequently used benchmarks to determine the level of physical fitness is through the pulse. This study aims to determine the effect of elderly gymnastics on the physical fitness of the elderly in Tanjung Village, Hamparan Rawang District, Sungaipuh City. This type of research is an experiment with a one-group pre-post test design. with a sample of 15 people or total sampling, the level of physical fitness is done by measuring the pulse at rest and exercise.Based on the results of the research and hypothesis testing conducted by the researchers, the results of the t-test resting pulse pre-test and post-test were tcount 80.769 while ttable 1.761 (tcount 80.769 > ttable 1.761) with a significant level α = 0.05 and the results of the t-test pulse pre-test and post-test exercises of tcount 23.469 while ttable 1.761 (tcount 23.469 > ttable 1.761) with a significant level α = 0.05 it can be concluded that